Comparison of the therapeutic effects of three internal fixation methods for transverse fractures of the patella - Xiao-Dong Li; Kewei Du (Frontiers in Surgery, 2025)
BackgroundThis study aimed to evaluate the treatment effects of three internal fixation methods, including tension band with K-wires, tension band with cannulated screws and tension band with ring-pins on transverse fractures of the patella.MethodsPatellar fracture patients treated in Shanghai Yangpu District Shidong Hospital from March 2016 to January 2023 were divided into three groups based on the internal fixation method: the ring-pins group (tension band with ring-pins), the K-wires group (tension band with K-wires), and the cannulated screws group (tension band with cannulated screws). Surgery duration, hemoglobin decrease, excellent rate of knee joint function evaluation at postoperative 3 months and 12 months, VAS scores before surgery and at 3 and 12 months after surgery, postoperative complication rate, and removal rate of internal fixation were compared among the three groups of patients.ResultsNo significant differences were observed in operation time and the degree of hemoglobin decrease before and after operation among the three groups (P > 0.05). There was a statistical difference in the excellent and good rate of Böstman's score among the three groups of patients 3 months after surgery (P < 0.05). The excellent and good rates of knee joint scores in the ring-pins group and the cannulated screws group in 3 months after surgery were higher than in the K-wires group, and no significant differences were observed in the excellent and good rates of Böstman's score among the three groups at 12 months after surgery (P > 0.05). No significant differences were observed in VAS scores across groups before and after surgery (P > 0.05). The VAS scores at 3 months and 12 months after surgery were lower than those before surgery (P < 0.001). Significant differences were observed in the incidence of postoperative complications (P < 0.05) and hardware removal rates (P < 0.001) among the three groups. The ring-pins group and the cannulated screws group had fewer postoperative complications than the K-wires group.ConclusionCompared with K-wires and cannulated screws, ring-pins have the advantages of wide application range, low postoperative complication rate, and easy removal of implants. Treatment experience, low surgical complexity, and good postoperative knee joint function recovery have obvious clinical application value.